Love for sale : pop music in America - Hajdu, David (Farrar, Straus and Giroux, 2016)
From the age of song sheets in the late nineteenth century to the contemporary era of digital streaming, pop music has been our most influential laboratory for social and aesthetic experimentation, changing the world three minutes at a time. Hajdu shows how pop has done much more than peddle fantasies of love and sex to teenagers. Exhaustively researched and rich with fresh insights, Love for Sale details pop music from Eva Tanguay, who upended Victorian conceptions of feminine propriety, to Blondie, the scandal of disco; from Bessie Smith and the 'blues queens' of the 1920s to Jimmie Rodgers, a former blackface minstrel performer who created the country music sound. At every turn, Hajdu surprises and challenges readers to think about our most familiar art in unexpected ways. --